Physical Persons as Participants in Customs Legal Relations within the Eurasian Economic Union - Sergey V. Khalipov (Московский журнал международного права, 2016)
The article analyses legal foundations and variations of participation of physical persons in customs legal relations. It scrutinizes the law of the Eurasian Economic Union and the Russian Federation legislation on customs. The Member States of the Eurasian Economic Union's regulations on the importation of goods to the customs territory by physical persons are considered. Peculiarities of making customs payments by physical persons, performing customs operations and exercising customs control are demonstrated.